Reply Of Soft Tıssue Chın To Orthodontıc Therapy In Subjects Wıth Dıfferent Growth Patterns - Lale Taner-Sarisoy; Nilüfer Darendeliler (Galenos Yayinevi, 2001)
The aim of the study is to evaluate the soft tissue chin changes of subjects with different growth patterns treated with extraction orthodontic therapy. Thirteen mesiodivergent and twenty hyperdivergent subjects were included in the study and they were treated by edgewise orthodontic therapy. Measurements were made on a coordinate system that was constructed after mandibular superimpositions were done on the lateral cephalometric films taken before and after treatment. As a result growth effects were eliminated. The changes within the groups were assessed by paired comparison t-test and the changes between the groups were assessed by student t-test. In assessment of the changes within the groups, no significant differences were found in the mesiodivergent group, whereas the sagittal change of B' value was found to be statistically significant in the hyperdivergent group. The differences between before and after orthodontic therapy in subjects with different growth patterns were not found to be significant between the groups. The reply of soft tissue chin to extraction orthodontic therapy in subjects with different growth patterns was not found to be different. It was concluded that the difference of soft tissue chin between the two groups was due to the different growth pattern type.